“US Boots on the Ground,” the Enemy, and Post-Cold War Presidential Rhetoric - Marta Kobylska (European Journal of American Studies)
This article is an investigation into the case of the enemy in American post-Cold War presidential rhetoric regarding the deployment of US ground troops to the fight overseas. It examines the links between the two themes from the perspective of Kenneth Burke’s rhetoric of identification and Annita Lazar and Michelle M. Lazar’s strategies of out-casting. A close analysis of presidential addresses to the nation announcing the deployment of American combat troops abroad is followed by a discussion of the implications of presidential rhetorical choices for active followership.